Influence of discrete fibre reinforcement on the uniaxial compression response and seismic wave velocity of a cement-stabilised sandy-clay - Cristelo, Nuno (2015)
A sandy clay from the northeast region of Portugal has been reinforced with polypropylene fibres and cement, and seismic wave velocity measurements and uniaxial compression strength tests were performed. Results showed that the fibre induce variations on the wave's velocity that cannot be related to real changes in the material stiffness. Therefore, care should be used when using this technique in fibre reinforced soils. The addition of fibres resulted in an increase of compression strength of the mixtures, for every cement content. Regarding the stiffness, the fibres proved to be increasingly effective with na increase in cementation, especially at the early stages of the stressestrain curve, when the secant deformability modulus increases with fibre content. However, no influence of the discrete reinforcement was detected on the peak and post-peak stages of the loading process. Fibre length showed also to be influential on strength and stiffness.